2003
DOI: 10.1016/s0140-6736(03)14021-4
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mortality of ischaemic heart disease among carriers of haemophilia

Abstract: SummaryBackground Coagulation plays an important part in ischaemic cardiovascular disease. Results of studies have shown that extremes in hypocoagulability protect against ischaemic cardiovascular disease. We have investigated overall mortality and death from cardiovascular causes in carriers of haemophilia, who in most cases have mildly decreased coagulability without clinical signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(48 citation statements)
references
References 20 publications
3
44
0
1
Order By: Relevance
“…The proportionate reductions in mortality from heart disease were virtually identical in severe and in moderate/mild hemophilia, at 38% and 37%, respectively (Table 4) and were similar to the value observed in a recent study of mortality from ischemic heart disease among carriers of hemophilia 25 (36%, based on 39 deaths). This argues against a gradually increasing protective effect as concentrations of factor VIII and IX decrease and in favor of a threshold effect.…”
Section: Mortality From Cardiovascular Diseasesupporting
confidence: 84%
“…The proportionate reductions in mortality from heart disease were virtually identical in severe and in moderate/mild hemophilia, at 38% and 37%, respectively (Table 4) and were similar to the value observed in a recent study of mortality from ischemic heart disease among carriers of hemophilia 25 (36%, based on 39 deaths). This argues against a gradually increasing protective effect as concentrations of factor VIII and IX decrease and in favor of a threshold effect.…”
Section: Mortality From Cardiovascular Diseasesupporting
confidence: 84%
“…In addition, mortality due to ischemic heart diseases (but not cerebral stroke) in both hemophilia A (FVIII deficiency) and hemophilia B (FIX deficiency) patients is actually lower compared with the general male population. 31,32 Data from the present study indicate that PAI-1 is also essential in maintaining cardiac homeostasis and microvascular integrity. Indeed, interstitial hemosiderin deposition, near the pericardium, as revealed by Prussian blue staining, was detected in younger PAI-1 Ϫ/Ϫ hearts, but not in WT hearts.…”
Section: Org Frommentioning
confidence: 66%
“…On the other hand, there were no major differences between siRNA and pharmacological modalities applied to fIXa as both could mimic the human hemophilia B observations (Sramek et al. 2003; Darby et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In one example, it has been reported that approximately 99–50% reduction in levels of fIX (as observed in moderate, mild hemophilia B patients and carriers of hemophilia B) are associated with a reduced risk of thrombosis (Sramek et al. 2003; Darby et al. 2007) for acceptable levels of bleeding.…”
Section: Introductionmentioning
confidence: 99%